Biochemical Perspective of Alcohol Prohibition in Islam and Implications on Legal Alcohol Content of Drinks in Islamic Countries - Ahmad Houri; Ali Safadi (Ar-Raniry: International Journal of Islamic Studies, 2016)
An analysis of the concepts of intoxication in blood and the required amount of alcohol to reach that level was analyzed from physiological and religious perspectives. The exact value of potentially allowed alcohol concentration was determined. The results indicate a BAC of 0.05% (w/v) as a set level for intoxication.  The determined pure alcohol amount required to reach this level was 27 g (for a 70 kg female) at least.  Accordingly, the determined allowed alcohol concentration is 0.45% (w/v) for what would be considered non-intoxicating.  This was compared to published results regarding the reported alcohol content of various foods and drinks. A sensitivity analysis was conducted to allow for variation in the considered BAC and the corresponding alcohol concentration in drinks.  An analysis of alcohol content in various cooked foods showed an interesting spread in the alcohol content. A review of set legal limits in some Islamic countries is recommended.